A modified sidereal filtering for mitigating the code measurement multipath effects of BeiDou GEO satellites. Issue 357 (2nd November 2017) - Wang, Xing; Liu, Wenxiang; Li, Baiyu; Sun, Guangfu
Abstract : Multipath delay is one of major error sources which limit global navigation satellite systems positioning accuracy. Due to the orbit characteristics, multipath effects are more evident on the code range observables of BeiDou Navigation Satellite System (BDS) geostationary earth orbit (GEO) satellites. We employed zero-phase filter to extract the low-frequency components of multipath series with the definite cutoff frequency and pass-band gain, and introduced a modified sidereal filtering for mitigating the multipath effects on code measurements of GEO satellites. The applications of this modified sidereal filtering show that the corrections for the standard deviation of code observables residuals on BDS B1, B2, and B3 frequency have reached more than 30, 22, and 14%, respectively. After resolving the GEO satellites code measurement multipath effects, the precisions of code-only single-point positioning were also improved.